2015
DOI: 10.19026/ajfst.8.1559
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Compensation Mechanism of Agricultural Water Resources: An Empirical Study in Zhejiang, China

Abstract: Ecological compensation is a new area in the field of resources environment. In this study, we set an empirical analysis model about ecological compensation mechanism and analyze influential factors based on agricultural perspective. The result shows that: first, loss of development opportunities is the most important factor that will affect ecological compensation, the regression coefficient is 0.071; sec, environmental protection cost is the most significant variable in ecological compensation, the sig value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…According to the existing problems in the ecological environment of the Chishui River, Qiu and Zhai (2014) established the ecological compensation mechanism. Based on the perspective of agricultural development, Hu (2015) concluded that the factors affecting the ecological compensation mechanism mainly include the loss of development opportunities, environmental protection cost, and public awareness. Yang et al (2020) analyzed the current situation of ecological compensation in the Yellow River basin, and described the framework of water-related ecological compensation in the Yellow River Basin in detail.…”
Section: Introductionmentioning
confidence: 99%
“…According to the existing problems in the ecological environment of the Chishui River, Qiu and Zhai (2014) established the ecological compensation mechanism. Based on the perspective of agricultural development, Hu (2015) concluded that the factors affecting the ecological compensation mechanism mainly include the loss of development opportunities, environmental protection cost, and public awareness. Yang et al (2020) analyzed the current situation of ecological compensation in the Yellow River basin, and described the framework of water-related ecological compensation in the Yellow River Basin in detail.…”
Section: Introductionmentioning
confidence: 99%